One-dimensional Anderson model with dichotomic correlation in the presence of external electric field - Kaya, T. (SPRINGER, 2008)
A one-dimensional diagonal tight binding electronic system with dichotomic correlated disorder in the presence of external d.c field is investigated. It is found numerically that the conductance distribution obeys fairly well to log-normal distribution in weak disorder strength in localized regime, which indicates validity of single parameter scaling theory in this limit. Contrary to the universal cumulant relation C-1 = 2C(2) in the absence of d.c. field, we demonstrated numerically that C-1 >> 2C(2) in the presence of the field in localized regime. We interpret this result as suppression of the fluctuation effects by the external field. In addition, it is obtained that the quantity NFc , here N is the system size and F (c) is the crossover field, decreases as the as the system energy E increases. Moreover, we find numerically a simple linear relation between the average logarithm of the conductance and the field strength as = C(N, lambda)F, here C(N, lambda) is a constant for particular values of N and lambda, which is the Poisson parameter of the dichotomic process.
Keywords: LOCALIZATION-DELOCALIZATION TRANSITION; BLOCH ELECTRONS; STARK LOCALIZATION; SCALING THEORY; WAVE-FUNCTIONS; ABSENCE; CHAINS; DIFFUSION; CRYSTALS; Physics